BVRI PHOTOMETRY OF 46 SOUTHERN BRIGHT STARS - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
We have made four color photometric observations (BVRI System) of 46 Southern Bright Stars, in order to enlarge, in right ascension, our previous Catalogue (Mendoza, 1967a).
BOL OBS TONAN TACUB
Keywords: BVRI, PHOTOMETRY, SOUTHERN, BRIGHT STARS; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOMETRIA